Chapter 24: The European Parliament as a gender equality actor: a contradictory forerunner - Kantola, Johanna (Edward Elgar Publishing, 2023)
This chapter analyses to what extent the European Parliament's political practices are supportive of gender equality and feminist governance. The chapter maps the formal institutional arrangements, which support gender equality within the institution and constitute important facets of feminist governance. These include a parliamentary committee, gender mainstreaming initiatives, gender action plans and sexual harassment policies. At the same time, there are a number of informal practices in the parliament, which have the potential to undermine the good formal practices and institutions for feminist governance. The chapter presents findings on opposition to gender equality in the parliament, which slows down good feminist governance practices and gender equality policies. Forms of opposition include: opposition to sexual harassment policies; direct and indirect opposition to gender equality and related policies by radical right populists; and institutional resistance to gender equality among the parliament as a whole and among established mainstream political groups.